Improvement of Project Monitoring Model Using A Combination of Quality Function Deployment and Lean Six Sigma at PT TEC - Muhamad Rezky Prasetyaji; Niniek Fajar Puspita; Tatang Akhmad Taufik (Eduvest - Journal of Universal Studies, 2025)
PT Tripatra Engineering and Construction (TEC) has transitioned its project monitoring system from manual methods to a cloud-storage-based system. However, the current system remains inadequate, often failing to provide accurate real-time data, leading to delays in decision-making. Challenges include data inconsistencies, complex interfaces, slow performance, adaptation difficulties, and integration issues. User feedback highlights work delays (23%) and cost overruns in procurement (1.2 times the budget), potentially causing company losses. This research analyzes user needs and proposes improvements using Quality Function Deployment (QFD) and Lean Six Sigma (LSS). The study develops a prototype EPC project monitoring system focusing on three key enhancements: Real-Time Mailing Distribution, Document Tracking, and User Monitoring Application. These improvements enhance information distribution, document tracking, and monitoring capabilities. The findings indicate that the improved system enhances interdisciplinary collaboration, decision-making quality, and workflow design, emphasizing value-added activities. Additionally, it facilitates real-time data processing to support strategic decisions and foster an adaptive work ecosystem. This prototype serves as a foundation for continuous improvement, operational support, and enhanced project execution effectiveness.